Hsp90 C-terminal domain inhibition enhances ferroptosis by disrupting GPX4-VDAC1 interaction to increase HMOX1 release from oligomerized VDAC1 channels - Jieyou Li; Guibing Wu; Hairou Su; Manfeng Liang; Shengpei Cen; Yandan Liao; Xiangjun Zhou; Guantai Xie; Zihao Deng; Wenchong Tan; Yan Li; Wang Xiao; et al. (Redox Biology)
Hepatocellular carcinoma (HCC) is one of the most common and lethal malignancies worldwide. Given the critical role of liver in iron storage and metabolism, ferroptosis, characterized by iron-dependent lipid peroxidation and oxidative damage, has become a potential therapy for HCC. Recent research indicated that Voltage-dependent anion-selective channel protein 1 (VDAC1), a key gatekeeper on the outer mitochondrial membrane (OMM), promotes ferroptosis in its oligomeric form. While oxidative stress is known to promote VDAC1 oligomerization, the relationship between oxidative modifications such as carbonylation and VDAC1 oligomerization remains poorly understood. Additionally, it is uncertain whether oligomerized VDAC1 channels facilitate the release of ferroptosis-related molecules. Our research discovered that the inhibition of the C-terminal domain of Heat shock protein 90 (Hsp90) reduced the protein level of Glutathione peroxidase 4 (GPX4) and decreased the interaction between GPX4 and VDAC1, consequently activating the carbonylation and oligomerization of VDAC1 through VDAC1-K274 site in a redox-dependent manner. The VDAC1 oligomerization promotes the release of Heme oxygenase-1 (HMOX1) from mitochondria into the cytoplasm, leading to iron overload and ultimately promoting ferroptosis. Thus, VDAC1 oligomerization is a critical factor in the pathway linking mitochondrial dysfunction to ferroptosis, highlighting the potential therapeutic interventions for HCC associated with iron dysregulation.